If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 24 = 4y + -6 Reorder the terms: 24 + 2y = 4y + -6 Reorder the terms: 24 + 2y = -6 + 4y Solving 24 + 2y = -6 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 24 + 2y + -4y = -6 + 4y + -4y Combine like terms: 2y + -4y = -2y 24 + -2y = -6 + 4y + -4y Combine like terms: 4y + -4y = 0 24 + -2y = -6 + 0 24 + -2y = -6 Add '-24' to each side of the equation. 24 + -24 + -2y = -6 + -24 Combine like terms: 24 + -24 = 0 0 + -2y = -6 + -24 -2y = -6 + -24 Combine like terms: -6 + -24 = -30 -2y = -30 Divide each side by '-2'. y = 15 Simplifying y = 15
| 36=2(x-5) | | 2Y(0.5x)=x-4 | | 12+4n=24+6n | | Z=-8i | | 3x-15+x=5 | | 0.2x^2-0.4x-1=1-3x | | 10-6y=12-8y | | 5y=x^2-2x-5 | | 4x+5=-21-5x | | 3.2p+4=2p-2 | | 3.2+4=2p-2 | | 6x-1=5(x+1) | | 14x+y=3*14 | | 2x+3-4=8x+3 | | y=(4sinx)(8cosx) | | 24/(4/3) | | 5*ln(2a-1)=15 | | x^4-6x^3+4x^2-24x=0 | | 3x^2-13(x-y)+4=0 | | (2/7)x=42 | | 3x^2y^2-13x-13y+4=0 | | 2x(x+1)=5-2x | | .05x+.1y=1 | | 0=3x^2-18-48 | | 9n+11=65 | | 2y+18+5y= | | 5x+10=8x | | 3x^4-4x^3+3=0 | | 7secx+7tanx=7 | | 5n-3+2n+6=3n+4-7n-9 | | 3(2x-6)=6(2x+1) | | 4+8=48 |